Fundraising Communication Model for the Development of Islamic Boarding Schools in Agam Regency - Ahmad, Fajri; Oktarina, Soraya (Universitas Muhammadiyah Mataram, 2025)
Abstrak: Pengembangan pondok pesantren di Kabupaten Agam tahun mulai 2021 mengalami kemajuan yang amat pesat, keberadaan pesantren sebagai agent of change suatu lembaga utama yang terdepan menciptakan moral anak bangsa. Fundraising pesantren dapat memainkan peran yang signifikan untuk pengembangan pesantren mulai mencari donatur masyarakat, lembaga dan pemerintahan. Penelitian ini bertujuan untuk mengeksplorasi model komunikasi fundraising efektif bagi pengembangan pondok pesantren, yang sering menghadapi keterbatasan dana untuk pengembangannya. Hasil penelitian menegaskan bahwa adanya peningkatan tiga tahun mulai tahun 2021 sampai sekarang pengembangan pondok pesantren di Kabupaten Agam dengan dukungan donatur dari masyarakat, perantau dan pemerintah di Kabupaten Agam. Beberapa poin kunci dari model komunikasi fundraising ialah keberadaan struktur organisasi yang jelas, tujuan dari pengembangan pondok pesantren dan strategi kebijakan pengumpulan donasi secara online dan ofline yang bertujuan memudahkan donatur memberikan donasi.. Abstract: The development of Islamic boarding schools in Agam Regency from 2021 will experience very rapid progress, the existence of Islamic boarding schools as agents of change, a main institution at the forefront of creating the morale of the nation's children. Islamic boarding school funding can play a significant role in the development of Islamic boarding schools, starting from looking for community, institutional and government donors. This research aims to explore effective fundraising communication models for the development of Islamic boarding schools, which often face limited funds for their development. The research results confirm that there has been a three-year increase from 2021 until now in the development of Islamic boarding schools in Agam Regency with the support of donors from the community, nomads and the government in Agam Regency. Several key points from the fundraising communication model are the existence of a clear organizational structure, the objectives of developing Islamic boarding schools and online and offline donation collection policy strategies which aim to make it easier for donors to make donations.